Influences of soil acidity on Streptomyces populations inhabiting forest soils. - Hagedorn, C (1976)
The Streptomyces populations inhabiting five acidic forest soils were examined. It was found that lowering the pH of a medium selective for streptomycetes (starch-casein agar) to the pH of the particular soil horizon being plated influenced both the total numbers and types of streptomycetes that were isolated from the soils examined in this study. On the acidified medium both the numbers of streptomycetes and the percentage of total bacteria on the plates represented by streptomycetes increased (as compared with the same medium with a pH of 7.2). These differences were greatest on the isolations from the most acid soils. The largest concentrations of streptomycetes were found in the surface horizon (0 to 15 cm) and the litter layer immediately over the surface mineral horizon. Acidity tolerance tests demonstrated that random samplings of isolates contained acidophilic, neutrophilic, and acidoduric strains, with the largest numbers of acidophiles being found on the acidified media from the most acid soils. There were no differences between overall utilization of selected carbohydrates among the isolates taken from either the neutral or acidic media, although a larger proportion of the acid media isolates produced acid from the carbohydrates. Evidence is presented which indicates that different types of streptomycetes were isolated on the acid media, and possible reasons for the presence of these acid-tolerant populations are discussed.